Smart Bureaucracy dalam Pelayanan Publik: Evaluasi Implementasi PTSP Digital pada Perizinan Bangunan di Jakarta Timur - Syafina Aulia Ryanta Putri; Neneng Sobibatu Rohmah (Majalah Ilmiah Dinamika Administrasi (MIDA), 2026)
This study analyzes the implementation of digital-based Pelayanan Terpadu Satu Pintu (PTSP) in the management of Izin Mendirikan Bangunan (IMB) in East Jakarta and evaluates its effectiveness within the framework of smart bureaucracy. The research aims to examine whether digitalization through the JAKEVO (Jakarta Evolution) platform reflects a structural transformation of bureaucracy toward data-driven governance. This study employs a qualitative case study approach conducted in East Jakarta. Informants consisted of PTSP officials, Unit Pelaksana Teknis Daerah (UPTD), and service users selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation.The findings indicate that digitalization has significantly improved service efficiency, transparency, accessibility, and administrative speed. The integration of JAKEVO with the Online Single Submission (OSS) system has reduced procedural fragmentation and strengthened interagency coordination. However, several challenges remain, including limited digital infrastructure capacity, low public digital literacy, and organizational resistance to change. Although digital PTSP implementation demonstrates procedural and operational transformation, it has not yet fully optimized strategic data utilization and real-time monitoring as required in a comprehensive smart bureaucracy model. In conclusion, digital PTSP in East Jakarta represents a substantial step toward smart bureaucracy, yet further institutional strengthening, data-driven policy integration, and public digital empowerment are necessary to achieve a fully adaptive and integrated bureaucratic system.